Imlplementasi GIS untuk Pemetaan Distribusi Mahasiswa KKM (Kuliah Kerja Masyarakat) Mahasiswa UNIKI Birueun - Munirwan, Amrullah (LPPM-UNIKI, 2021)
A data collection system for the location of KKM students is needed to find out the distribution locations of studentswhich can be done by creating a system in the form of geographic information. GIS is a mapping that can display thelocation directly regarding the location of groups and KKM members in each batch. The design of the system with thePHP programming language and My-SQL database as well as for the mapping system using the Google Maps API which can display the earth's geographic information through the help of an internet connection to a Google server. The dataused are student data, supervising lecturers, and the location of the KKM village. The results of the research achievedare that the system can display the distribution of KKM students spread throughout the districts of Bireuen, BenerMeriah and North Aceh and students can also access information and provide information on KKM activities in eachgroup.